To pay or not to pay ; Heavenly vision ; Lounging around [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
A look at the issues surrounding the country's debt. Some debt cap educators made it an election issue. Mother Mary reminds people to repent and pray the rosary through communication with a Korean woman Julia. A look also at music lounges.